El reto de la investigacion intercultural: la traduccion de lo politicamente correcto - del Rosario Martín Ruano, María (Hermēneus (Soria, Spain), 2001)
Recent developments in Translation Studies argue for a comprehensive notion of translation as cross-cultural mediation and discursive transfer. The subsequent research, necessarily interdisciplinary, may benefit from the highly criticised discipline of Corpus Linguistics, if based on intercultural assumptions. Analysis of the Spanish cultural translation of the American discourse of political correctness will illustrate this hypothesis. (Author abstract)